Updating the Coupling Algorithm between HYDRUS and MODFLOW in the HYDRUS Package for MODFLOW - Beegum, S. (2020)
In this model, after every MODFLOW time step, the flux at the bottom of the HPM profile is given as an input recharge flux to MODFLOW. MODFLOW simulates groundwater flow, and the water table depth at the end of the MODFLOW time step is assigned as the bottom boundary condition in the HPM profile. The current coupling algorithm assumes that the groundwater table in the HPM profile remains constant throughout the entire MODFLOW time step. This results in unrealistic sudden inflow and/or outflow fluxes at the bottom of the HPM profile after every time step. The objective of this study was to develop a methodology to eliminate the error in the determination of the recharge flux at the bottom of the HPM profile. This was achieved by updating or modifying the pressure head profile in the HPM profile after every MODFLOW time step. The effectiveness and the applicability of the new coupling algorithm were evaluated using different case studies. The new coupling algorithm is effective in eliminating unrealistic sudden variations in the bottom flux in the HPM profiles.